2023
DOI: 10.26668/businessreview/2023.v8i5.1969
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compensation, Labor Insurance, and Old Age Guarantee on Employee Satisfaction in Government Institutions

Abstract: Purpose: This study aims to find out how the effect of compensation (X1), labor insurance (X2), and old-age insurance (X3) on employee job satisfaction (Y) in a government institution. Nowadays Government Institutions are trying to continuously manage the existence of their employees so that they can work better and can show good work performance so that the organizational goals can be achieved optimally. One of the steps that can be taken is by providing compensation to employees, as well as providing labor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Because, at this level, an important aspect is the pedagogical praxis itself, so digitalization has also arrived, allowing it to be a relevant element now. And, to the extent that it continues to deepen, the pedagogical competences of teachers linked to problem solving are vital, for which it is necessary to know how to select the information, translate it into relevant and pertinent content, but, above all, know how to communicate them, always taking into account the levels of security that this implies, that is, data protection, intellectual protection, among other aspects (To Nugroho & Bandono, 2023;Gómez-Galán et al, 2021;Palos-Sánchez et al, 2023;Niño-Cortés et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Because, at this level, an important aspect is the pedagogical praxis itself, so digitalization has also arrived, allowing it to be a relevant element now. And, to the extent that it continues to deepen, the pedagogical competences of teachers linked to problem solving are vital, for which it is necessary to know how to select the information, translate it into relevant and pertinent content, but, above all, know how to communicate them, always taking into account the levels of security that this implies, that is, data protection, intellectual protection, among other aspects (To Nugroho & Bandono, 2023;Gómez-Galán et al, 2021;Palos-Sánchez et al, 2023;Niño-Cortés et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…and Bandono, A. ( 2023) conducted a study of 167 government employees, which demonstrated that employee benefits such as workers' compensation insurance and pensions also have a positive impact on employee job satisfaction [8]. Therefore, it can be concluded that salary as well as subsidies can be used as a motivational element to increase the level of job satisfaction and engagement of employees.…”
Section: Salary and Benefitsmentioning
confidence: 99%